(3fRgI GdeTJGb aj GNJQGb GdBaGbs - (3GdEOQjSj , eMeO Hf eMeO Hf YHO Gddg Hf EOQjS GdMSfj GdWGdHj, CHh YHO Gddg,J (B560 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdYXeI hGdSdWGf hGdWhd hGdEeJfGf GdaVd hGdCfYGe s
(3BNQgG (B:s
(3hLejY fHGJ gPG GdLHd EfeG gh fHGJ GdHbe hjNQL Edi SGjQ GdCbWGQ s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B24 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B236s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1947s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs